(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Aims: The aim of the study deals with the design, development, and comparative stability studies of optimized formulations as well as potential formula and process optimization trials of novel orlistat liposomal dispersion. All the experimental studies were evaluated for stability study profiles with respect to physical and chemical key parameters such as physical appearance, pH, density, drug entrapment efficiency, drug content, particle size, polydispersity index and zeta potential. The stability study was carried out at different temperature storage conditions. Materials and Methods: Formula optimization studies were utilized to investigate the impact of different molar ratios of orlistat, soya phosphatidylcholine, and cholesterol. Process optimization studies were also performed to comprehend the effect of variable stirring time, sonication time, and centrifugation time on the physical and chemical factors. Orlistat liposomal formulations were prepared using ethanol injection method. Results and Discussion: Percentage entrapment efficiency of F30 and F31 has 90.6 Â± 0.3% and 89.0 Â± 0.2% and average particle size of 847.9 nm and 848.1 nm, respectively, and rest of the physical and chemical parameters were satisfactory. Conclusions: The basic aim of the study was achieved with maximum % entrapment efficiency with smaller particle size. The optimized formulations have satisfactory physicochemical parameters at the initial time point and retained similar during stability at long-term storage conditions up to 6 months. Optimized formulations were stable up to 1 month at accelerated storage condition, but there was a significant change observed at 2 and 3 months.